Up‐gradient eddy fluxes of potential vorticity near the subtropical jet. Issue 22 (19th November 2013) - Birner, T.; J. Thompson, D. W.; Shepherd, T. G.
<x xml:space="preserve">Abstract</x> [1] The role of eddy fluxes in the general circulation is often approached by treating eddies as (macro)turbulence. In this approach, the eddies act to diffuse certain quasi‐conservative quantities, such as potential vorticity (PV), along isentropic surfaces in the free atmosphere. The eddy fluxes are determined primarily by the eddy diffusivities and are necessarily down‐gradient of the basic state PV field. Support for the (macro)turbulence approach stems from the fact that the eddy fluxes of PV in the free atmosphere are generally down‐gradient in the long‐term mean. Here we call attention to a pronounced and significant region of up‐gradient eddy PV fluxes on the poleward flank of the jet core in both hemispheres. The region of up‐gradient (i.e., notionally "antidiffusive") eddy PV fluxes is most pronounced during the winter and spring seasons and partially contradicts the turbulence approach described above. Analyses of the PV variance (potential enstrophy) budget suggest that the up‐gradient PV fluxes represent local wave decay and are maintained by poleward fluxes of PV variance. Finite‐amplitude effects thus represent leading order contributions to the PV variance budget, whereas dissipation is only of secondary importance locally. The appearance of up‐gradient PV fluxes in the long‐term mean is associated with the poleward shift of the jet—and thus the region of wave decay relative to wave growth—following wave‐breaking events.